Survey of Perceptions and Practices among Canadian Gastroenterologists regarding the Prevention of Venous Thromboembolism for Hospitalized Inflammatory Bowel Disease Patients - Roshan Razik; Charles N Bernstein; Justina Sam; Reka Thanabalan; Geoffrey C Nguyen (Canadian Journal of Gastroenterology)
BACKGROUND: Patients with inflammatory bowel disease (IBD) who are hospitalized with disease flares are known to be at an increased risk of venous thromboembolism (VTE). This is a preventable complication; however, there is currently no standardized approach to the prevention and management of VTE.